Neurophysiological Effects of Trait Empathy in Music Listening - Wallmark, Zachary; Deblieck, Choi; Iacoboni, Marco (Frontiers in Behavioral Neuroscience, 2018)
The social cognitive basis of music processing has long been noted, and recent research has shown that trait empathy is linked to musical preferences and listening style. Does empathy modulate neural responses to musical sounds? We designed two fMRI experiments to address this question. In Experiment 1, subjects listened to brief isolated musical timbres while being scanned. In Experiment 2, subjects listened to excerpts of music in four conditions (familiar liked/disliked and unfamiliar liked/disliked). For both types of musical stimuli, emotional and cognitive forms of trait empathy modulated activity in sensorimotor and cognitive areas: in the first experiment, empathy was primarily correlated with activity in SMA, IFG, and insula; in experiment 2, empathy was mainly correlated with activity in prefrontal, temporo-parietal, and reward areas. Taken together, these findings reveal the interactions between bottom-up and top-down mechanisms of empathy in response to musical sounds, in line with recent findings from other cognitive domains.